Hand function and self‐care in children with cerebral palsy. (22nd December 2020) - Burgess, Andrea; Boyd, Roslyn N; Chatfield, Mark D; Ziviani, Jenny; Wotherspoon, Jane; Sakzewski, Leanne
Abstract : Aim: To examine the relationship between self‐care and bimanual performance in children aged 8 to 12 years with cerebral palsy (CP). Method: This was a cross‐sectional study of 74 children with CP (unilateral n =30, bilateral n =44; 48 males, 26 females; median age 9y 8mo [25th, 75th centiles 9y 1mo, 10y 8mo], Manual Abilities Classification System level I=30, II=28, III=16). Self‐care was measured using the Pediatric Evaluation of Disability Inventory–Computer Adaptive Test (PEDI‐CAT), and bimanual performance using the Assisting Hand Assessment (AHA) and Both Hands Assessment (BoHA). Measures of cognition, behavioural regulation, inattention, and gross motor function were included. Analyses used a directed acyclic graph to select variables for linear regression modelling. Results: Higher AHA and BoHA scores were associated with higher PEDI‐CAT scores. An increase of 1 AHA unit was associated with an increase of 0.12 PEDI‐CAT scores, and a 1 BoHA unit increase was associated with an increase of 0.17 PEDI‐CAT scores. The BoHA accounted for 57% of variance in PEDI‐CAT scores for children with bilateral CP, while BoHA and cognition accounted for 68% of variance. The AHA accounted for 40% of variance in PEDI‐CAT scores for unilateral CP with no effect of cognition on self‐care. Interpretation: Self‐care was strongly and positively associated with bimanual performance. Associations between self‐care and bimanual performance differed for those with unilateral and bilateral CP. What this paper adds: There is a strong positive relationship between self‐care and bimanual performance for unilateral and bilateral cerebral palsy (CP). Both Hands Assessment (BoHA) scores have a stronger association with self‐care than Assisting Hand Assessment scores. BoHA scores also account for more variation in self‐care. There is a strong positive relationship between self‐care and cognition overall. The effect of cognition on self‐care performance differed for bilateral and unilateral CP. What this paper adds: There is a strong positive relationship between self‐care and bimanual performance for unilateral and bilateral cerebral palsy (CP). Both Hands Assessment (BoHA) scores have a stronger association with self‐care than Assisting Hand Assessment scores. BoHA scores also account for more variation in self‐care. There is a strong positive relationship between self‐care and cognition overall. The effect of cognition on self‐care performance differed for bilateral and unilateral CP. Video Podcast: https://youtu.be/Ws6C_MKvVpE This article is commented on by Konigorski on page 498 of this issue.